Characterizing polarized frequencies of tremor episodes at Copahue volcano (Southern Andes): A case study. (October 2022) - Melchor, Ivan; Almendros, Javier; Caselli, Alberto
Abstract: The characterization of dominant frequencies is essential for tracking significant temporal variations during and between tremor episodes. In this work, we proposed a method for quantifying the dominant frequencies and their attributes. We applied it to characterize three tremor episodes recorded several hours before ash emissions at Copahue volcano during June–August 2020. The method consisted in (i) extracting dominant peaks (relative maximum in successive PSD) and their polarization attributes: polarization degree, rectilinearity, and polarization angles; and (ii) extracting dominant frequencies (i.e., relative maximums in the PDF of dominant peaks) and their polarization attributes. We applied the method at three stations located at 4.5, 9.5, and 11 km from the crater vent to investigate how the characteristics for dominant frequencies change among the stations. We found linearly polarized peaks in the three stations whose azimuth coincides with crater direction. The station closest to the crater (NAN5) recorded linearly polarized frequencies above 3.0 Hz. The time evolution of dominant peaks suggests that different sources compose the seismic tremor. Our results represent a forward step in the understanding of eruptive tremors of Copahue, being a clear example that their implementation at other volcanoes can improve the monitoring tasks.